The Effect of Reaction Temperature on the Quality of Oyster Enzymatic Hydrolysate Maillard Products - Peng, Huiyi; Huang, Yuni; Huang, Jiating; Cao, Dianxuan; Lin, Yijun; Tang, Haixia; Chen, Xueren; Yang, Zhao (Transactions on Environment, Energy and Earth Sciences, 2024)
Oyster meat was used as raw material, which was enzymatically digested under specific conditions for 3h. Then the effect of reaction temperature on the sensory, color difference, reaction rate, and volatile flavor components of the oyster enzymatic hydrolyzates and glucose meridian reaction product was investigated. The study showed that the 3h enzymatic hydrolysis of oyster produced the best flavour and sensory score of the maillard reaction product at 110 (110HM), which had the absorbance value of 0.788 for A294, and 0.606 for A420. 54 compounds were identified from 110HM, which mainly contained 6 alcohols (26.40%), 3 ketones (1.80%), 8 aldehydes (8.38%), 6 esters (1.71%), 16 hydrocarbons (32.84%), and 15 heterocyclic and other species (22.82%).